2021
DOI: 10.1073/pnas.2017925118
|View full text |Cite
|
Sign up to set email alerts
|

The SHREAD gene therapy platform for paracrine delivery improves tumor localization and intratumoral effects of a clinical antibody

Abstract: The goal of cancer-drug delivery is to achieve high levels of therapeutics within tumors with minimal systemic exposure that could cause toxicity. Producing biologics directly in situ where they diffuse and act locally is an attractive alternative to direct administration of recombinant therapeutics, as secretion by the tumor itself provides high local concentrations that act in a paracrine fashion continuously over an extended duration (paracrine delivery). We have engineered a SHielded, REtargeted ADenovirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…The multiple cloning site (MCS) of the pShuttle vector was replaced with synthetic MCS modules, called MCS1 or MCS2, by Gibson Assembly (New England Biolabs). The synthetic MCS1 module contained, from 5′ to 3′, the CMV promoter, Nhe I restriction site, Xho I restriction site, and polyadenylate [poly(A)] site from bovine growth hormone as previously described ( 20 ). The MCS2 module contained, from 5′ to 3′, the SV40 promoter, Spe I restriction site, Sal I restriction site, and poly(A) site from SV40.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The multiple cloning site (MCS) of the pShuttle vector was replaced with synthetic MCS modules, called MCS1 or MCS2, by Gibson Assembly (New England Biolabs). The synthetic MCS1 module contained, from 5′ to 3′, the CMV promoter, Nhe I restriction site, Xho I restriction site, and polyadenylate [poly(A)] site from bovine growth hormone as previously described ( 20 ). The MCS2 module contained, from 5′ to 3′, the SV40 promoter, Spe I restriction site, Sal I restriction site, and poly(A) site from SV40.…”
Section: Methodsmentioning
confidence: 99%
“…To define a model system for local IL-12 therapy that reflects these clinical findings, we used a nonreplicative, shielded, and retargeted AdV5 vector previously established in our laboratory (20)(21)(22). For this study, human epidermal growth factor receptor 2 (HER2) was used as a model antigen to target the HER2-overexpressing syngeneic tumor cell lines B16-HER2 and EMT6-HER2.…”
Section: Il-12 Immunotherapy Prompts Nk Cells To Orchestrate An Antit...mentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we have focused our work on in vitro applications and shown their usefulness for cell culture assays. As the next step, future studies should be conducted focusing on an in-depth analysis of in vivo approaches ,, of the new modular adapters.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, 3D imaging with the CUBIC system is suitable for analysis of complex vascular structures in vivo. Indeed, some studies recently reported the use of tissue-clearing methods for visualizing blood and lymphatic capillaries in mouse [16][17][18][19][20][21][22][23] .…”
mentioning
confidence: 99%